2014
DOI: 10.1097/sap.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Oral Clefts Among Different Ethnicities in the State of California

Abstract: Our results suggest different incidence rates among different ethnicities. We found the highest rates for any oral cleft, isolated cleft palate, and cleft lip with and without palate in the white (non-Hispanic) population. The declining incidence rates during the period of the study (15 years) could be attributed to environmental, demographic, or gene pool factors. However, further studies are needed to investigate this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 12 publications
4
31
0
Order By: Relevance
“…An observed decline in prevalence for CLP, and not for CP alone, was observed by others (Chang et al, ; Rozendaal et al, ; Saad et al, ). Rozendaal et al observed a decrease in CLP, however as we observed, they did not detect a statistically significant decline in CP alone (Rozendaal et al, ).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…An observed decline in prevalence for CLP, and not for CP alone, was observed by others (Chang et al, ; Rozendaal et al, ; Saad et al, ). Rozendaal et al observed a decrease in CLP, however as we observed, they did not detect a statistically significant decline in CP alone (Rozendaal et al, ).…”
Section: Discussionsupporting
confidence: 58%
“…Rozendaal et al observed a decrease in CLP, however as we observed, they did not detect a statistically significant decline in CP alone (Rozendaal et al, ). Prior population‐based studies have described a declining prevalence of oral clefts among different ethnicities(Saad et al, )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cubans and Asians, especially Chinese and Asian Indians, had either lower or similar rates of these defects compared with Europeans . Other studies on birth defects providing data on ethnic variation also suggest the existence of racial disparities in children with selected CMs …”
Section: Ethnicity Disparities In Pregnancy Outcomes In General Populmentioning
confidence: 96%
“…9 Other studies on birth defects providing data on ethnic variation also suggest the existence of racial disparities in children with selected CMs. 10,11 2.2 | Pregnancy complications/maternal outcomes Maternal ethnic background has been found to be an important contributor to pregnancy outcomes and complications in the general population.…”
mentioning
confidence: 99%